2007
DOI: 10.4049/jimmunol.179.8.5326
|View full text |Cite
|
Sign up to set email alerts
|

A Population of CD19highCD45R−/lowCD21low B Lymphocytes Poised for Spontaneous Secretion of IgG and IgA Antibodies

Abstract: Ab responses to selected Ags are produced by discrete B cell populations whose presence and functional relevance vary along the ontogeny. The earliest B lineage-restricted precursors in gestational day 11 mouse embryos display the CD19+CD45R/B220− phenotype. Phenotypically identical cells persist throughout gestation and in postnatal life, in parallel to the later-arising, CD19+CD45R+ B cells. Very early after birth, the CD19+CD45R− B cell subset included high frequencies of spontaneously Ig-secreting cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 61 publications
(53 reference statements)
2
28
0
Order By: Relevance
“…CBA/N mice bearing the btk mutation exhibited a 30-50% reduction in FO cells and a severe reduction of B1a and B1b subpopulations. We confirmed that btk-deficient CBA/N mice contained very few 19 + 45R lo cells in these structures, suggesting a strong btk dependency of these cells, as reported elsewhere (23). However, 19 + 45R lo cells did not express CD11b or CD5 (Fig.…”
Section: Lymphoid Organ Distribution and Postnatal Progression Of 19 supporting
confidence: 76%
See 4 more Smart Citations
“…CBA/N mice bearing the btk mutation exhibited a 30-50% reduction in FO cells and a severe reduction of B1a and B1b subpopulations. We confirmed that btk-deficient CBA/N mice contained very few 19 + 45R lo cells in these structures, suggesting a strong btk dependency of these cells, as reported elsewhere (23). However, 19 + 45R lo cells did not express CD11b or CD5 (Fig.…”
Section: Lymphoid Organ Distribution and Postnatal Progression Of 19 supporting
confidence: 76%
“…In the spleen, this population could be clearly distinguished from the Transitional cell subsets, conventional MB cells, ABC, and B1 cells. These observations, together with our previous confocal microscopy findings demonstrating a perifollicular distribution of 19 + 45R lo cells (23), suggest that these cells represent a B cell subset of embryonic origin.…”
Section: Lymphoid Organ Distribution and Postnatal Progression Of 19 mentioning
confidence: 60%
See 3 more Smart Citations